Speaking activities used to cope with students' Low oral proficiency - Cabrera Martínez, Ricardo; vides de Guzmán, Claudia Marina; Mora Marín, Ileana; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2010)
As English Foreign Language (EFL) teachers, the authors of this Action Research have observed that most teachers (including the authors) working in Foreign Language Department (FLD) at the University of El Salvador in charge of the courses aimed at developing the four macro skills: Listening, Speaking, Reading, and Writing (also called Intensive Courses) do not do much to help those students who show a low level of oral proficiency in the target language due to different reasons, such as: overcrowded classrooms, many hours spent dedicated to administrative duties, and the like. The syllabus of the courses mentioned above is usually designed to state the levels that students are going to move on according to the American Council on the Teaching of Foreign Languages (ACTFL) guidelines which are the guidelines currently followed by the teachers in charge of Intensive Courses. Different activities are planned to help take those students to the highest level that has been planned. Different evaluations are designed throug hout the course to measure student’s progress and, at the end of the semester; a passing grade is assigned to those students who are ready for the next course.
Anexos: Grades and averages of experimental group, Grades and averages of control group, Advanced i syllabus, Conversation club syllabus, Time table for conversation club, Weekl y report of activities, actfl guidelines.
Tesis graduated work presented to obtain the degree of -- (Maestría en Didáctica del Idioma Inglés) -- Universidad de El Salvador, San Salvador, 2010
Bibliografía : hojas : 27-28
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Pronunciación; Métodos de enseñanza